Evaluation of public–private partnerships: A life-cycle Performance Prism for ensuring value for money - Liu, H.; Love, Peter; Smith, J.; Sing, M.; Matthews, Jane (2018)
© The Author(s) 2018. Public–private partnerships have become an integral strategy to deliver infrastructure projects in Australia. Yet, public–private partnerships have been plagued with controversy due to recurrent time and cost overruns. The paucity of an approach to evaluate the performance of public–private partnerships throughout their life-cycle has hindered the ability of governments to manage their effective and efficient delivery. This paper examines the practice of evaluation for a hospital and prison that were delivered using public–private partnerships. The empirical evidence indicates that with public–private partnerships: (1) performance is typically measured during the construction and operation phases using time, cost and quality and a restricted number of key performance indicators; and (2) a process-based and stakeholder-oriented measurement approach would be better suited to evaluate performance. Building upon the extant literature and the findings emerging from ‘practice’ (i.e. actual activity, events or work), a Performance Prism for ameliorating the evaluation of public–private partnerships throughout their lifecycle is proposed. The research presented in this paper provides stakeholders of public–private partnerships, especially governments, with a robust framework for governing and future proofing their assets to ensure value for money.